Taxonomical study on genus Solanum(Solanaceae) in Taif region, Saudi Arabia - Fadl, Mohamed A.; Alamer, Khalid H.; Alharth, Mona A.; Hassan, Walaa A.; Korany, Shereen M.; Al-Yasi, Hatim M.; Alsherif, Emad A. (Phytotaxa, 2023)
The taxonomy and phylogeny of Solanum species are unnerving tasks because of their wide range and huge size. This work aims to reassess the taxonomy of Solanum species in the Taif Highlands based on numerical criteria. We used 43 accessions and 99 macro- and micro-morphological traits to identify nine Solanum species and five hybrids from the S. nigrum complex. The obtained results showed that Solanum species in the studied area belong to three subgenera with five sections: Subgenus Leptostemonum with sections Oliganthes (S. forskalii and S. glabratum), Melongena (S. incanum and S. melongena), and Giganteiformia (S. schimperianum); Subgenus Solanum with sections Solanum (S. nigrum and S. villosum); and Subgenus Potatoe section Petota (S.lycopersicum). In addition, the pollen characters separated spiny species (S. incanum, S. melongena, S. glabratum, and S. forskalii) from non-spiny species (S. schimperianum, S. lycoperiscum, S. nigrum, and S. villosum). The present study recommends an elaborate study of the hybridization between S. villosum and Solanum nigrum, also, experiments for hybridization between cultivated and wild species need more investigation.